The Influence of Leadership, Motivation, and Work Environment on Company Performance at PT PLN (Persero) Sektor Pembangkitan Belawan - Lubis, Andrew Satria; Kumalasari, Fauziah; Parluhutan, Taufik Akbar; Lubis, Muhammad Arif (Talenta Publisher, 2025)
This study investigates the influence of leadership, motivation, and work environment on company performance at PT PLN (Persero) Sektor Pembangkitan Belawan. Employing a quantitative associative approach, the research utilizes multiple linear regression analysis to examine the relationships among variables. The population comprises 74 employees, with the entire population serving as the sample through a total sampling technique. Data were collected using a Likert-scale questionnaire and analyzed using SPSS software. The results reveal that leadership, motivation, and work environment each have a positive and significant effect on company performance, both partially and simultaneously. The regression equation derived is: Y = 3.203 + 0.275X₁ + 0.263X₂ + 0.197X₃. The model's Adjusted R² value is 0.619, indicating that 61.9% of the variance in company performance can be explained by the three independent variables. These findings underscore the critical role of human resource factors in enhancing organizational performance.​ The study contributes to the literature on organizational behavior and human resource management by highlighting the significance of leadership, motivation, and work environment in driving company performance. It also provides practical insights for managers aiming to improve organizational outcomes through strategic human resource interventions.